Phytochemical ingredients and Pharmacological potential of Calendula officinalis Linn. - Pawan Kumar Verma; Rajinder Raina; Sanjay Agarwal; Harpreet Kaur (Mazandaran University of Medical Sciences, 2018)
Calendula officinalis Linn. commonly known as marigold has long history of usage by the folklore system. It has a high economic value as herbal medicine and is widely used in cosmetics, perfumes, dyes, pharmaceutical preparations and food products for centuries. The plant has been approved for food use and appears in the food and drug administration (FDA) list of generally recognized as safe (GRAS) substances. The literature available for the comprehensive review study were taken from the different worldwide accepted scientific database, journals, books for botanical description, pharmacological properties and ethno-botanical uses of C. officinalis Linn. Natural products containing calendula either as extract or oil are complex mixtures containing hundreds of biologically active constituents such as carotenoids, flavonoids, saponins, sterols, phenolic acids, lipids, amino acids, carbohydrates, etc. These phytoconstituents have wide applicability in food and cosmetic industries besides their therapeutic applications viz. as antioxidant, antimicrobial, anti-inflammatory, anti-ulcer, anti-proliferative, antiparasitic, hypoglycemic, hypolipidemic and wound healing potential in experimental and clinical trials. Being useful therapeutic agents in their own right, an understanding of these traditional medicines has provided new plant derived drug leads to modern medicine for therapeutic application.